AUTONOMOUS INTERPRETATION BY THE ECtHR AND HARMONISATION OF NATIONAL PRIVATE LAW: CHALLENGES AND LIMITS - Халабуденко, Олег (SWorldJournal, 2025)
This article investigates the transformative role of the European Court of Human Rights (ECtHR) in the harmonization of national private law within member states. It highlights how the ECtHR, through its principle of autonomous interpretation, defines leg